Children's folklore: a source book - Sutton-Smith, Brian, editor; Mechling, Jay, editor; Johnson, Thomas W., editor; McMahon, Felicia R., editor; Utah State University Press, publisher (Colorado State University. Libraries, 1999)
A collection of original essays by scholars from a variety of fields--including American studies, folklore, anthropology, psychology, sociology, and education--Children's Folklore: A Source Book moves beyond traditional social-science views of child development. It reveals the complexity and artistry of interactions among children, challenging stereotypes of simple childhood innocence and conventional explanations of development that privilege sober and sensible adult outcomes. Instead, the play and lore of children is shown to be often disruptive, wayward, and irrational. The contributors variably consider and demonstrate contextual and "textual" ways of studying the folklore of children. Avoiding a narrow definition of the subject, they examine a variety of resources and approaches for studying, researching, and teaching it. These range from surveys of the history and literature of children's folklore to methods of field research, studies of genres of lore, and attempts to capture children's play and games".--Provided by publisher.
Introduction: What Is Children's Folklore? / Brian Sutton-Smith -- Who Are the Folklorists of Childhood? / Sylvia Ann Grider -- Overview: History of Children's Folklore / Brian Sutton-Smith -- The Complexity of Children's Folklore / Rosemary Levy Zumwalt -- The Transmission of Children's Folklore / John H. McDowell -- Overview: Methods in Children's Folklore / Brian Sutton-Smith -- Double Dutch and Double Cameras: Studying the Transmission of Culture in an Urban School Yard / Ann Richman Beresin -- Children's Games and Gaming / Linda A. Hughes -- Methodological Problems of Collecting Folklore from Children / Gary Alan Fine -- Overview: Children's Folklore Concerns / Brian Sutton-Smith -- Songs, Poems, and Rhymes / C.W. Sullivan III -- Riddles / Danielle M. Roemer -- Tales and Legends / Elizabeth Tucker -- Teases and Pranks / Marilyn Jorgensen -- Overview: Settings and Activities / Brian Sutton-Smith -- Children's Lore in School and Playgrounds / Bernard Mergen -- Material Folk Culture of Children / Simon J. Bronner -- Children's Folklore in Residential Institutions: Summer Camps, Boarding Schools, Hospitals, and Custodial Facilities / Jay Mechling -- Conclusion: The Past in the Present: Theoretical Directions for Children's Folklore / Felicia R. McMahon, Brian Sutton-Smith -- Bibliography of Children's Folklore / Thomas W. Johnson, Felicia R. McMahon.
Keywords: Children -- Folklore; Folklore -- Methodology